The Ino80 chromatin-remodeling complex restores chromatin structure during UV DNA damage repair. - Sarkar, S; Kiely, R; McHugh, P (2010)
Chromatin structure is modulated during deoxyribonucleic acid excision repair, but how this is achieved is unclear. Loss of the yeast Ino80 chromatin-remodeling complex (Ino80-C) moderately sensitizes cells to ultraviolet (UV) light. In this paper, we show that INO80 acts in the same genetic pathway as nucleotide excision repair (NER) and that the Ino80-C contributes to efficient UV photoproduct removal in a region of high nucleosome occupancy. Moreover, Ino80 interacts with the early NER damage recognition complex Rad4-Rad23 and is recruited to chromatin by Rad4 in a UV damage-dependent manner. Using a modified chromatin immunoprecipitation assay, we find that chromatin disruption during UV lesion repair is normal, whereas the restoration of nucleosome structure is defective in ino80 mutant cells. Collectively, our work suggests that Ino80 is recruited to sites of UV lesion repair through interactions with the NER apparatus and is required for the restoration of chromatin structure after repair.